Comparison of pre- and post-contrast-enhanced attenuation correction using a CAIPI-accelerated T1-weighted Dixon 3D-VIBE sequence in 68Ga-DOTATOC PET/MRI. Issue 139 (June 2021) - Bruckmann, Nils Martin; Lindemann, Maike E.; Grueneisen, Johannes; Grafe, Hong; Li, Yan; Sawicki, Lino M.; Rischpler, Christoph; Herrmann, Ken; Umutlu, Lale; Quick, Harald H.; Schaarschmidt, Benedikt Michael
Abstract: Objectives: To investigate the influence of contrast agent administration on attenuation correction (AC) based on a CAIPIRINHA (CAIPI)-accelerated T1-weighted Dixon 3D-VIBE sequence in 68 Ga-DOTATOC PET/MRI. Material and methods: Fifty-one patients with neuroendocrine tumors underwent whole-body 68 Ga-DOTATOC PET/MRI for tumor staging. Two PET reconstructions were performed using AC-maps that were created using a high-resolution CAIPI-accelerated Dixon-VIBE sequence with an additional bone atlas and truncation correction using the HUGE (B0 homogenization using gradient enhancement) method before and after application of Gadolinium (Gd)-based contrast agent. Standardized uptake values (SUVs) of 21 volumes of interest (VOIs) were compared between in both PET data sets per patient. A student's t -test for paired samples was performed to test for potential differences between both AC-maps and both reconstructed PET data sets. Bonferroni correction was performed to prevent α-error accumulation, p < 0.0024 was considered to indicate statistical significance. Results: Significant quantitative differences between SUVmax were found in the perirenal fat (19.65 ± 48.03 %, p < 0.0001), in the axillary fat (17.46 ± 63.67 %, p < 0.0001) and in the dorsal subcutaneous fat on level of lumbar vertebral body L4 (10.26 ± 25.29 %, p < 0.0001). Significant differences were also evident in the lungs apical (5.80 ± 10.53 %, p < 0.0001), dorsal at the level of the pulmonary trunk (15.04 ± 19.09 %, p < 0.0001) and dorsal in the basal lung (51.27 ± 147.61 %, p < 0.0001). Conclusion: The administration of (Gd)-contrast agents in this study has shown a considerable influence on the AC-maps in PET/MRI and, consequently impacted quantification in the reconstructed PET data. Therefore, dedicated PET/MRI staging protocols have to be adjusted so that AC-map acquisition is performed prior to contrast agent administration.